Rare and common manifestations of COVID‐19 in children. Issue 1 (18th February 2022) - Colonna, Cristiana; Restano, Lucia; Monzani, Nicola A.; Zussino, Martina; Ponziani, Alessandra; Cambiaghi, Stefano; Cavalli, Riccardo
Abstract: Introduction: It has been almost 2 years since the first reports on cutaneous manifestations of COVID‐19. Those reported in children are different and include macular, papular, lichenoid, vesicular, urticarial, and vascular morphologies, among others. The prognosis of isolated cutaneous involvement in COVID‐19 in children is usually self‐limiting but the extreme variety of clinical presentations complicates the clinical approach. Methods: Numerous reviews have been systematically drafted and edited giving the clinicians a future direction for skin presentations during pandemics. Results and Discussion: Hereby we report the rare and common manifestations of COVID‐19 in children and question the recurrence phenomena and age‐related distribution of the eruptions. Abstract : Age distribution of SARS‐Cov‐2 positive or suspected paediatric patients (0−18 years) observed in our centre during the first pandemic spread categorized by cutaneous manifestations. In the lower part of the figure, boxes correspond to the highest frequency rate of patients with the clinical characteristics mentioned. Lateral strings include all the sample spans. CLLs, chilblain‐like lesions (COVID toes); EM‐like, erythema multiforme‐like; MIS‐C, multisystem inflammatory syndrome; PLEVA‐like, papular‐purpuric dermatitis of childhood.